Management Functions of Library and Archives Department of Tanjung Balai - Annisa, Astrie; Rohani, Laila (International Journal of Cultural and Social Science, 2023)
This research was conducted at the Library and Archives Service of Tanjung Balai City. The purpose of this study was to determine the controlling management functions and facilities of the Tanjung Balai City Library and Archives Service. This research is a descriptive study using a qualitative approach, data collection techniques with observation, interviews and documentation. In this study, 5 librarians and users at the Library and Archives Service of Tanjung Balai City became informants. The results of this study indicate that the Library and Archives Service of Tanjung Balai City in terms of the management function controlling the facilities is still lacking because the procurement of facilities is hampered due to an inadequate budget at the library. Another factor is the lack of controlling management. Library staff at the Tanjung Balai City Library and Archives Service only use makeshift facilities that can still be used and only depend on the budget from the Tanjung Balai City government.